Political concepts : a critical lexicon - Ophir, Adi; Stoler, Ann Laura; Gourgouris, Stathis, 1958-; Anidjar, Gil; Spivak, Gayatri Chakravorty; Balibar, Étienne, 1942-; Copjec, Joan; Lezra, Jacques, 1960-; Kalyvas, Andreas, 1967-; Bernstein, J. M. (Idiom (Fordham University Press), 2018)
Essays by major contemporary figures in political philosophy, anthropology, and cultural studies presenting an original reflection on the question what is a particular concept (classic concepts in politics as well as newly politicized concepts) and asking what sort of work a rethinking of that concept can do for us now.